Paired and Unpaired Passing Practice Against the Ability of Passing the Ball in Football Games - Sudirman Sudirman (UNIVERSITAS NEGERI MAKASSAR, 2022)
This study aims to determine the effect of paired and unpaired ball passing exercises on ball passing skills in soccer games. This research is an experimental research type. The population of this study was all students of SMA Negeri 1 Wonomulyo Polman Regency with a total sample of 30 male students who were selected by random sampling. The data analysis technique used is an inferential analysis technique with a t-test using the SPSS Version 22.00 system at a significant level of 95% or 0.05. Starting from the results of data analysis, this study concludes that: (1) there is a significant effect of pair ball passing practice on the ability to pass the ball in soccer games, it is proven to = 5,200 > tt = 2,045 (P < 0,05); (2) there is a significant effect of unpaired ball passing practice on the ability to pass the ball in football games, it is proven to = 3.200 > tt = 2.045 (P < 0.05); (3) there is a significant difference in the effect of paired and unpaired ball passing exercises on the ability to pass the ball in a soccer game, proven to = 3.238 > tt = 2,000 (P < 0.05).